Analysis of The Influence of Enterprise Resources Planning Adoption and Information Technology Applications on Quality of Accounting Report - Dermawan Sembiring, Lenny; Anastasia Putri, Juan; Atmojo, Kunto; Tridianty Sianipar, Ruth; Hendrawan, Henky (Jurnal Informasi dan Teknologi, 2024)
This study aims to ascertain how user skills, information technology utilization, and enterprise resource planning (ERP) adoption affect accounting report quality. Causal study methodology is employed in this work. The method for gathering data was a questionnaire. The study's respondents are employees who have used accounting information systems. Convenience sampling, or non-probability sampling, was used to choose the sample for this study. Multiple linear regressions are employed in this study. According to the research findings, the use of enterprise resource planning, information technology, and user knowledge together had a favorable and significant effect on the quality of accounting information. The quality of accounting information can be enhanced by ERP adoption when backed by top management commitment and support, ease of system integration, system capacity to meet needs, vendor training, and solutions that satisfy needs. The quality of accounting information is positively impacted by IT, which is supported by a solid infrastructure, including functionally matched computers, computer networks, internet access, effective accounting procedures, software-assisted data processing, information system output, and infrastructure upkeep. Furthermore, the quality of accounting information can be enhanced by solid user knowledge, reinforced by education, training, and user experience. When managing accounting information systems, businesses must consider these criteria to guarantee that the data generated is reliable, accurate, timely, comprehensive, and verifiable. Thus, companies can make better decisions based on accurate and relevant information.